2018
DOI: 10.3389/fmicb.2018.02327
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Fungal and Plant Communities Differ Between Desert and Grassland in a Typical Dryland Region of Northwest China

Abstract: The relationships between soil fungal and plant communities in the dryland have been well documented, yet the associated difference in relationships between soil fungal and plant communities among different habitats remains unclear. Here, we explored the relationships between plant and fungal functional communities, and the dominant factors of these fungal communities in the desert and grassland. Soil fungal functional communities were assessed based on fungal ITS sequence data which were obtained from our pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…In surface ecosystems, biotic and/or abiotic properties of the soil and land use, including type of vegetation cover, modify the diversity of communities to varying degrees [14,[22][23][24][25][26]. Meteorological factors, such as temperature, relative humidity, and precipitation, have also been said to influence sporulation and the dispersion of fungi [27].…”
Section: Introductionmentioning
confidence: 99%
“…In surface ecosystems, biotic and/or abiotic properties of the soil and land use, including type of vegetation cover, modify the diversity of communities to varying degrees [14,[22][23][24][25][26]. Meteorological factors, such as temperature, relative humidity, and precipitation, have also been said to influence sporulation and the dispersion of fungi [27].…”
Section: Introductionmentioning
confidence: 99%
“…Bradford et al, 2019; Franklin et al, 2016; Fernandez et al, 2016, Kyaschenko et al, 2017). Climate parameters and edaphic factors influence relative abundances and species composition of plant and microbial communities (Castaño et al, 2018; Op De Beeck et al, 2015; Wang et al, 2018). Hostile environments challenge species and survival requires contemporary local adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…The most important field-measured variable for modelling fungal dark diversity was plant species richness which was negatively related to dark diversity in both open habitats and woodlands. Plant richness and composition are well-known to correlate with fungal richness and composition (Zak et al 2003, Chen et al 2017, Yang et al 2017, Brunbjerg et al 2018, Wang et al 2018), and sites with lower plant species richness have previously been found to have a relatively higher proportion of plants in the dark diversity (Fløjgaard et al 2020). Here, the negative relation between plant richness and fungal dark diversity may be attributed to greater plant richness frequently associated with more stable communities and ecosystems (Kuiters 2013, Pellkofer et al 2016, Yang et al 2018), which could indicate longer continuity and hence time for fungi to establish.…”
Section: Discussionmentioning
confidence: 99%